Geomorfologi Tanah Pada Transisi Geologi Formasi Wonosari dan Nglanggran di Kecamatan Purwosari Gunungkidul Yogyakarta - Indra Agus Riyanto; Ahmad Cahyadi; Dwi Sismoyo; Azura Ulfa; Wilda Aulia Fathoni; Ghalih Nur Wicaksono (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
The transition zone of the Wonosari and Nglanggran Formation in Purwosari District has the characteristics of thick soil, steep slopes, and no outcrops. The different characteristics found in the Wonosari Formation Zone are characterized by polygonal karst formations with thin soil and limestone rocks, and the Nglanggran Formation in the form of thick soil, andesite rock outcrops, and steep slopes. Geomorphological mapping of the Nglanggran and Wonosari Formation can be done easily through morphological approaches and outcrops. Geomorphological mapping is quite difficult to do in the transition of the Wonosari and Nglanggran Formation because it does not have outcrops and is difficult to interpret from morphology. Soil geomorphological approach needs to be done to define landform units for areas that do not have outcrops dan difficult to interpret through morphology. The purpose of this study was to map the geomorphological distribution of soil characteristics in the geological transition zone. The methods used to identify landform units are morphological delineation and soil survey. The morphological delineation for landform units was obtained from aerial photographs. The results of the delineation of landforms from aerial photographs are detailed by soil surveys. The results of the delineation of landforms using aerial photography produce high resolution, smooth, and firm compared to other sources. The results of the delineation of landforms from aerial photos obtained two units of landforms, limestone karst hills, Wonosari formation and andesitic rocky hills, Nglanggran formation. There is a transitional transition zone in the TP7 soil sample with the color change from dark brown (karst) to light brown (old volcanic). The thickness of the soil in the old volcanic is more than 1 meter and deeper than the karst soil (< 60 cm). The transition zone has three soil horizons A, B, and B/C which are classified as more developed than the karst region (A and B horizons). The soil texture in old volcanic is clay and silt, while the dominant karst area is clay.